An orthotropic multi-surface damage-plasticity FE-formulation for wood: Part I – Constitutive model. (November 2020) - Benvenuti, E.; Orlando, N.; Gebhardt, C.; Kaliske, M.
Highlights: The present study formulates a novel FE constitutive model with multi-surface plasticity and anisotropic multi-surface damage. The model correctly captures the sensitivity of the material to loading-directionality, and ductile and brittle phenomena. We define a set of plasticity and damage activation criteria and three damage variables corresponding to distinct stress states. We formulate the algorithmic treatment of the relevant tangent constitutive matrix. We show that the proposed formulation performs better than analogous existing models. Abstract: Restoration of ancient wooden beams and design of smart wood-based structures are gaining an increasing interest in building industry. In this context, the computational challenge is to develop numerical constitutive models that account for the complex and strongly non-linear behaviour of wood. Wood is a natural composite exhibiting pronounced orthotropic behaviour, and markedly different properties along the parallel and transverse-to-the-fiber directions. It displays a strongly non-linear mechanical behavior, almost elasto-plastic at compressive loadings and elasto-damaging when subjected to tensile and shearing stresses. We devise here a novel constitutive model for wood with a multi-surface failure domain resulting from a set of plastic laws for compressive failure modes and orthotropic damage laws for tensile/shear failure modes. The advantage over existing formulations is that the coexistence of anisotropic damage and plasticity constitutive laws allows to correctly capture brittle failure induced by strain localization as well as the possible occurrence of ductile plastic behavior. Furthermore, the present contribution shows how to numerically treat the simultaneous presence of anisotropic damage and plasticity in a general algorithmic multi-surface framework. It is shown that the obtained numerical results satisfactorily fit to experimental data.